2004
DOI: 10.1160/th03-07-0481
|View full text |Cite
|
Sign up to set email alerts
|

Is prolonged immobilization a risk factor for symptomatic venous thromboembolism in elderly bedridden patients?

Abstract: Prolonged immobilization and advanced age are considered to be important risk factors for venous thromboembolism (VTE). Nevertheless, the need for VTE prophylaxis in long-term bedridden patients is not known. To assess whether very prolonged immobilization (i.e. over three months) carries an increased risk for clinically apparent VTE, we performed a historical-cohort study of nursing home residents during a ten-year period. Data concerning patient's mobility and incidence of overt deep vein thrombosis or pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…Furthermore, the analysis was restricted to the first 3 weeks only. However, it should be noted that: (i) the median duration of reduced mobility was 7 days; (ii) in all recent thromboprophylaxis trials, the primary efficacy end-point was assessed between 2 and 3 weeks after inclusion [4][5][6]; (iii) thromboprophylaxis in medical patients is recommended for up to 2 weeks [7]; and (iv) the 3-week incidence rate of venous thromboembolism reported in our study is similar to the 1-year incidence rate reported in a recent study in nursing home residents [28]. Another limitation is the fact that approximately 20% of symptomatic events were not confirmed using an objective test.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, the analysis was restricted to the first 3 weeks only. However, it should be noted that: (i) the median duration of reduced mobility was 7 days; (ii) in all recent thromboprophylaxis trials, the primary efficacy end-point was assessed between 2 and 3 weeks after inclusion [4][5][6]; (iii) thromboprophylaxis in medical patients is recommended for up to 2 weeks [7]; and (iv) the 3-week incidence rate of venous thromboembolism reported in our study is similar to the 1-year incidence rate reported in a recent study in nursing home residents [28]. Another limitation is the fact that approximately 20% of symptomatic events were not confirmed using an objective test.…”
Section: Discussionsupporting
confidence: 75%
“…[24][25][26][27] Gomes and colleagues found an incidence of 1.30 events per 100 PY, 24 Gatt et al found an incidence of 1.4 to 1.6 per 100 PY, 25 and Leibson and colleagues found an incidence of 1.2 to 1.5 per 100 PY. 26 These studies, however, relied on nursing home administrative data and diagnostic codes, and were, therefore, subject to diagnostic uncertainty and misclassification.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…We do not even know the level of risk for VTE in these patients or the real risk factors. Advanced age and limited mobility alone are insufficient reasons for prescribing prophylaxis [4] but it is important to identify among elderly chronic patients with reduced mobility those with additional factors that raise their risk profile for VTE.…”
Section: Introductionmentioning
confidence: 99%